The associations between low abundance of Mycoplasma hominis and female fecundability: a pregnancy-planning cohort study - Xiang Hong; Jiechen Yin; Wei Wang; Fanqi Zhao; Xiaoling Ding; Hong Yu; Xuening Zhang; Bei Wang (BMC Microbiology, 2022)
Abstract Objective To explore the impact of pre-pregnancy vaginal Mycoplasma hominis (M. hominis) colonization of low abundance on female fecundability. Methods In total, 89 females participating in a pre-pregnancy health examination program were included, and their pregnancy outcomes were followed up for 1 year. Vaginal swabs were collected, 16S rRNA genes were sequenced, and M. hominis colonization was confirmed by qPCR. Cox models were used to estimate the fecundability odds ratio (FOR) for women with M. hominis. Results The prevalence of M. hominis was 22.47% (20/89), and the abundance was relatively low (the cycle thresholds of the qPCR were all more than 25). In terms of the vaginal microbiome, the Simpson index of the positive group was significantly lower than that of the negative group (P = 0.003), which means that the microbiome diversity appeared to increase with M. hominis positivity. The relative abundance of M. hominis was negatively correlated with Lactobacillus crispatus (rho = − 0.24, P = 0.024), but positively correlated with Gardnerella vaginalis, Atopobium vaginae and Prevotella bivia (P all < 0.05). The cumulative one-year pregnancy rate for the M. hominis positive group was lower than that in the negative group (58.96% vs 66.76%, log-rank test: P = 0.029). After controlling for potential confounders, the risk of pregnancy in the M. hominis positive group was reduced by 38% when compared with the positive group (FOR = 0.62, 95% CI: 0.42–0.93). Conclusion The vaginal colonization of M. hominis at a low level in pre-pregnant women is negatively correlated with female fecundability.